MODEL KEHIDUPAN HARMONI DAN RUKUN MASYARAKAT MULTIAGAMA SERTA ETNIS DESA LABUAJA MAROS - Sampara Palili (STIT Sunan Giri Bima, 2024)
The article explores the harmonious and peaceful life of the multi-religious and multi-ethnic community of Labuaja Village, depicting the process of implementing a harmonious and peaceful life and the implications of such an implementation in daily practices. This study is a field research employing a descriptive qualitative approach. It utilizes a phenomenological approach and gathers data through direct observation, interviews, and documentation at the research location. Based on the data obtained, it was found that the harmonious and peaceful life of the multi-religious and multi-ethnic community of Labuaja Village can be realized due to several factors: 1) The cooperative attitude among community members is very enthusiastic in creating a harmonious and peaceful life, 2) The attitude of mutual respect and tolerance is very evident in the daily life of the Labuaja community, who do not question religion or ethnicity and build good relationships within the framework of family, brotherhood, unity, and togetherness, and 3) The attitude of caring for others is clearly seen in the involvement and participation in community activities. Furthermore, the implementation of the harmonious and peaceful life model in Labuaja Village is practiced in three environments: the family environment, the community environment, and the school environment.